Impact of natural resources rents on green growth: evidence from G7 countries - Qian, Jiangyunze; Chen, Lai (Frontiers in Environmental Science, 2025)
Climate change has become a global issue in the 21st century due to the excessive use of non-renewable energy sources. To mitigate this issue, the world has been shifting towards green growth. For this purpose, researchers and policymakers are struggling to explore the factors that significantly impact green growth. Although several determinants of green growth have been investigated in the available literature, the impact of (dis)-aggregated natural resources rents (i.e., minerals rent, coal rent, oil rent, natural gas rent, and total natural resources rent) have been scantly investigated. To fill this gap, this study aims to examine the impact of coal rent, oil rent, minerals rent, natural gas rent, and total natural resources rent on the green growth in G7 countries. The findings from the panel ARDL approach elucidate that coal rent, natural gas rent, and total natural resources rent have a negative impact on green growth in the long-run. Further, oil rent has a positive impact, while minerals rent has an insignificant impact on green growth in the long-run. The study proposes several policy recommendations based on the findings.